Manufacturing Process beyond Conventional Plasticity Theory: Case Study in Manufacturing Low Spring Index Coil - Prawoto, Yunan; Manville, Sonia; Sakai, T; Tanaka, M; Gnauple-Herold, T (Jurnal Internasional Penelitian Teknologi Terapan, 2020)
In the academic world, conventional plasticity theory limits the cold process due to energy inefficiency, material properties and residual stress that may inhibit the quality of a product, and therefore usually not recommended. However, industrial competition pushes that limits against the edge. Knowing the consequences in advance helps reducing the damage that may have been caused by such a violation. This paper shows an example in the form of a case study. A coil spring with a very low spring index that academically suggested to be made using hot process was attempted to be manufactured using cold coiling machine. The case study shows that although it is possible, extra careful and timely handling must be done to successfully manufacture it. A coil with excessive residual stress is shown in this paper. That residual stress alone was capable in damaging the coil during manufacturing. The defect takes place after coiling and before tempering process. A fracture mechanics was used to analyze the failure, which is the splitting due to excessive residual stress. The case study also shows that the problem can be solved by speedy and subsequent stress relieve annealing process.